Deaths in Sports and Forensic Medicine - Pündük, Zekine; Can, Muhammet (The Bulletin of Legal Medicine, 2023)
It is reported that sport is a multidisciplinary field with multi-dimensional interactions and scientific researches in terms of education, physiology, economy, pharmacology, sociology, psychology, philosophy, medicine, politics, law, communication and technological contents. Sudden death due to sports is defined by the World Health Organization as deaths occurring during or after sports activity, the signs of death appearing within half a minute to six hours and death occuring within 24 hours without any external factor. Athletes’ deaths during matches or training have been encountered with increasing frequency in recent years. Therefore, sudden deaths caused by sports or exercise are met with concern in the society. Most athlete deaths are caused by the cardiovascular system. The most common causes are known as hypertrophic cardiomyopathy, arrhythmogenic right ventricular dysplasia, and congenital coronary artery anomalies. However, coronary artery disease deaths are more common among athletes over the age of 35. Recently, with the Coronavirus disease-2019 (COVID-19) pandemic, deaths occurring during sports have also gained different dimensions. In this study, it was aimed to discuss the most common causes of deaths during sports activities, including the COVID-19 pandemic, and what should be done in terms of postmortem forensic medicine.